SPATIAL ALTERATION AT UBUD TRADITIONAL VILLAGE, GIANYAR, BALI IN THE GLOBALIZATION ERA: A CULTURAL STUDY - Artha Ardhana Sukawati, Tjokorda Oka; -, Sulistyawati; Parimartha, I Gde; Suastika, I Made (E-Journal of Cultural Studies, 2012)
In the era of globalization much spatial alteration has taken place at Ubud TraditionalVillage, Gianyar Regency, Bali as the consequence of fast development of tourism. The aspectswhich have changed, as the result of the shift from agricultural culture to tourism culture since1970, include the spatial relationship between man and God (parhyangan), the spatial relationshipbetween man and his environment (palemahan), and the spatial relationship between man and hisfellow being or the three things which cause physical and spiritual prosperity among human beings.This research in cultural studies was conducted to reveal the spatial alteration which hadtaken place at Ubud Traditional Market in the globalization era especially since 1970 as theconsequence of the fast development in tourism. The data were analyzed by applying qualitativeanalysis technique, eclecticism of the theory of change, the theory of space, the theory ofhegemony, and critical and practical theories. The research was conducted by employing qualitativemethod which features cultural studies.The results of the research show that the increase in population and in what is needed bytourism has led to the spatial alteration in parhyangan in the village and home levels. The spatialalteration in pawongan as a unity of membership (krama) does not take place and the spatialalternation in families does not either. This indicates that Ubud Traditional Village is getting morecomplex in facing modern and global condition with its commercial culture. Its tradition,agricultural culture and nature have contributed to the development of tourism. In regard topalemahan, catus patha has not been the only center of orientation any more. The settlement of thepopulation has followed the development of tourist facilities. Tourism has also altered the landusefulness causing zero-settlement based on groups of banjar (neighborhood under a traditionalvillage) to be irrelevant. In regard to the patterns of space occupied by families, the walls built toseparate one family from another have been demolished; the buildings (bale) have beenrehabilitated, teba (the unoccupied part of a compound where animals raised for sale are usuallykept and rubbish are usually gathered) has been exploited. The change in people’s behavior frombeing non commercial into commercial has blurred the layout and function of the buildings built inthe zones of madya (immediate level) and nista (lower level).
Keywords: spatial alteration, globalization, tourism, Tri Hita Karana, Ubud Traditional Village